LATIHAN TRICEP EKSTENSION DAN LATIHAN LONCAT TALI DAPAT MENINGKATKAN KEMAMPUAN SMASH DALAM PERMAINAN BOLA VOLI - Hidayat, Muhammad Ryan; Muhaimin, Ali; Muhsan, Muhsan (Gelora : Jurnal Pendidikan Olahraga dan Kesehatan IKIP Mataram, 2021)
Volleyball, which is included in team play, requires a combination or combination of skills possessed by each individual player in an effort of good teamwork so that they can score points and block attacks from opponents so as not to give points by passing, blocking. and smash. Volleyball players are also required to master good smash techniques because smash techniques are the determining factor for victory in volleyball games, tactics, physical and mental, and enthusiasm. Based on the results of observations made by researchers to all students. Researchers looked at students when playing with less body resistance, speed and power when smashing. The purpose of this study was to see the effect of tricep extension and jumping rope training on the ability to smash in volleyball games for extracurricular students at MTsN 5 Central Lombok in 2020. The research design used was experimental research, the researcher used two independent variables and one experimental variable. is the extencion and jump rope level while the dependent variable is the smash ability. The population used was 14 people, 7 did the trincep extencion exercise and 7 did rope jumping exercises, the instrument used was Nurhasan from the results of the pre-test and post-test data collection, the details of the t count was 6,885> t table 1,771 at significant level 5 % then there is an effect of tricep extension training on smash ability in volleyball for MTsN 5 Central Lombok extracurricular students in 2020 and t count 6,111> t table 1,771 at a significant level of 5% so there is an effect of rope jumping training on smash skills in volleyball on MTsN 5 middle lombok extracurricular students in 2020